Biomolecular and isotopic evidence reveals key cellular controls on methylmercury fate during bacterial mercury methylation - Jin-Ping Xue; Rémy Guyoneaud; Zoyne Pedrero; Luisa Maria Malberti-Quintero; Alina Kleindienst; Emmanuel Tessier; Océane Asensio; David Point; David Amouroux (Journal of Hazardous Materials, 2026)

Ocean productivity and trophic structure drive patterns of mercury accumulation in deep-pelagic fauna - Leandro N. Eduardo; Anaïs Médieu; Arnaud Bertrand; Julianna L. Santana; Flávia Lucena-Frédou; David Point; Guilherme V.B. Ferreira; Anne Lorrain; Anne K.S. Justino; François Le Loc'h; Jean-Marie Munaron; Laure Laffont; et al. (Science of The Total Environment, 2026)

Diffusive gradient in thin film for ultra-trace methylmercury measurements in the coastal and open sea - Isalyne Blondet; Fanny Rioual; Michelle I. Graco; Jesús Ledesma; Kevin Ruiz-Diaz; Arturo Aguirre-Velarde; Jonathan Flye-Sainte-Marie; Laure Laffont; Lars-Eric Heimbürger-Boavida; Natalia Torres-Rodriguez; Sophie Bonnet; Cécile Guieu; et al. (Marine Pollution Bulletin, 2026)

Biogeochemical Assessment of Trace Metal and Mercury Pollution in Two Tropical Estuaries Impacted by Multiple Pollution Sources - Ítala Gabriela Sobral dos Santos; Alex Souza Lira; David Point; Anaïs Médieu; Clístenes Williams Araújo do Nascimento; Leandro N. Eduardo; Flávia Lucena-Frédou (Biological Trace Element Research, 2025)

In situ measurement of trace sulfide concentrations in marine coastal waters using diffusive gradient in thin film passive samplers - Kevin Diaz; David Point; Wilson Carhuapoma; Astrid Avellan; Maricarmen Igarza; Jesús Ledesma; Fanny Rioual; Michelle Graco (Marine Chemistry, 2025)

Mercury compound-specific stable isotope fractionation in high-altitude lake ecosystems of the Bolivian Altiplano - Jérémy Masbou; David Point; Sylvain Bouchet; Jeroen E. Sonke; Carlos Molina; Carla Ibanez; Anne Lorrain; Julio Pinto; Dario Acha; David Amouroux (Science of The Total Environment, 2025)

Sulfides as environmental stressors in Paracas Bay, Peru - Fanny Rioual; Jonathan Flye-Sainte-Marie; David Point; François Colas; Tomasa Cuellar-Martinez; Jorge Tam; Kevin Diaz; Wilson Carhuapoma; Michelle Graco; Fred Jean; Arturo Aguirre-Velarde (Marine Pollution Bulletin, 2025)

Mercury biomagnification and trophic structure patterns in neotropical coastal estuaries impacted by a Chlor-alkali plant in northeast Brazil - Andréa P. Viana; François Le Loc’h; Thierry Frédou; Flávia Lucena-Frédou; Frédéric Ménard; Christelle Lagane; Jean-Marie Munaron; Alex S. Lira; Ítala G.S. dos Santos; Valdimere Ferreira; Júlio G. Gonzalez; David Point (Regional Studies in Marine Science, 2023)

Do marine protected areas influence mercury exposure? Insights from a shark community in the tropical Northeast Pacific - Gaël Le Croizier; Anne Lorrain; Mauricio Hoyos-Padilla; James T. Ketchum; Felipe Amezcua-Martínez; François Le Loc'h; Jean-Marie Munaron; Gauthier Schaal; David Point (Environmental Pollution, 2023)

Are tunas relevant bioindicators of mercury concentrations in the global ocean? - Anaïs Médieu; Anne Lorrain; David Point (Ecotoxicology, 2023)

Revealing the environmental pollution of two estuaries through histopathological biomarkers in five fishes from different trophic guilds of northeastern Brazil - Ítala Gabriela Sobral dos Santos; Alex Souza Lira; Caroline da Silva Montes; David Point; Anaïs Médieu; Clístenes Williams Araújo do Nascimento; Flávia Lucena-Frédou; Rossineide Martins da Rocha (Marine Pollution Bulletin, 2023)

Trends in tuna carbon isotopes suggest global changes in pelagic phytoplankton communities - Anne Lorrain; Heidi Pethybridge; Nicolas Cassar; Aurore Receveur; Valérie Allain; Nathalie Bodin; Laurent Bopp; C. Anela Choy; Leanne Duffy; Brian Fry; Nicolas Goñi; Brittany S. Graham; et al. (Global Change Biology, 2020)
Considerable uncertainty remains over how increasing atmospheric CO 2 and anthropogenic climate changes are affecting open‐ocean marine ecosystems from phytoplankton to top predators. Biological time series data are thus urgently needed for the world's oceans. Here, we use the carbon stable isotope composition of tuna to provide a first insight into the existence of global trends in complex ecosystem dynamics and changes in the oceanic carbon cycle. From 2000 to 2015, considerable declines in δ 13 C values of 0.8‰–2.5‰ were observed across three tuna species sampled globally, with more substantial changes in the Pacific Ocean compared to the Atlantic and Indian Oceans. Tuna recorded not only the Suess effect, that is, fossil fuel‐derived and isotopically light carbon being incorporated into marine ecosystems, but also recorded profound changes at the base of marine food webs. We suggest a global shift in phytoplankton community structure, for example, a reduction in 13 C‐rich phytoplankton such as diatoms, and/or a change in phytoplankton physiology during this period, although this does not rule out other concomitant changes at higher levels in the food webs. Our study establishes tuna δ 13 C values as a candidate essential ocean variable to assess complex ecosystem responses to climate change at regional to global scales and over decadal timescales. Finally, this time series will be invaluable in calibrating and validating global earth system models to project changes in marine biota.

Environmental conditions increase growth rates and mortality of zebra mussels (Dreissena polymorpha) along the southern invasion front in North America - Christopher J. Churchill; David J. Hoeinghaus; Thomas W. La Point (Biological Invasions, 2017)

Association of a Specific Algal Group with Methylmercury Accumulation in Periphyton of a Tropical High-Altitude Andean Lake - William G. Lanza; Darío Achá; David Point; Jeremy Masbou; Lucia Alanoca; David Amouroux; Xavier Lazzaro (Archives of Environmental Contamination and Toxicology, 2017)

(Methyl)Mercury, Arsenic, and Lead Contamination of the World’s Largest Wastewater Irrigation System: the Mezquital Valley (Hidalgo State—Mexico) - Stéphane Guédron; Céline Duwig; Blanca Lucia Prado; David Point; Marizol Giovana Flores; Christina Siebe (Water, Air, & Soil Pollution, 2014)